Operative Temperature Variance and Life Cycle Assessment Impacts of Wall Construction Materials (International Journal of Built Environment and Sustainability, 2023)
The overdependence on concrete in the construction industry in sub-Saharan African countries limits the potential use of sustainable materials in the construction of buildings. Hollow Concrete Block (HCB), the industry’s most widely used wall material, contributes to excessive carbon emissions and environmental degradation. Moreso, constructions that employ HCBs, specifically in Nigeria, severely threaten the indoor comfort levels in Naturally Ventilated Spaces NVSs. This study relies on quantitative data to analyse the impact of alternative wall materials in a case building in northern Nigeria. Mud bricks (MB) and Timber/brick (TB) were compared with the existing concrete (CW) case building. The study uses Meteonorm 8 and Climate Consultant 6.0 for EPW file generation. At the same time, dynamic thermal simulation and comparative experiments for thermal comfort and carbon emissions were conducted using DesignBuilder V6 and OneClick Lifecycle assessment tools, respectively. Modelled and simulated under NVS conditions using ASHRAE’s PMV model, the result of the study suggests that the MB alternative, although with an intermediate U-value of 0.318 W/m²k, accounts for the best indoor comfort temperature annually. While the CW building accounts for 41.31% of hours above the comfort temperature of 28⁰C, the TB and MB alternatives account for 29.99% and 27.37% of hours, respectively. Furthermore, the MB alternative is the most environmentally friendly material with 510 KgCO₂/m² emissions, a value 26% less than the CW building with an embodied carbon benchmark of 690 KgCO₂/m² during the building’s life cycle stages. The author suggests that mud construction’s thermal properties and Global Warming Impact (GWI) make it a better alternative to concrete and timber buildings in the tropics.
Keywords: Low Carbon, Operative Temperature, Embodied Carbon, Life cycle Assessment, Nigeria